Using mouse embryonic fibroblast (MEF) as feeder cells for production of embryonic stem cell (ESC) line in the murine and caprine / Goh Siew Ying - Goh, Siew Ying (2012)
Embryonic stem cells (ESC) have unlimited potential in the field of biological sciences and regenerative medicine due to their pluripotency and ability to self-renew indefinitely. With the goal to establish, isolate and culture murine (mESC) as well as caprine (gESC) embryonic stem cells, in vivo- and in vitro-derived blastocysts were used as a source in producing mESC and gESC lines. Both mESC and gESC were cultured in vitro using mouse embryonic fibroblast (MEF) as feeder cell layer in this study. The aims of this study were: a) to compare the effects of murine strain, blastocyst stage and inner cell mass (ICM) isolation techniques on the efficiency of deriving murine embryonic stem cell (mESC) lines in murine species and b) to compare the effects of in vivo- and in vitro-derived blastocyst sources as well as to establish effective technologies to isolate and culture ESC in caprine species. Mouse embryonic fibroblasts (MEF) were derived from murine foetuses (13.5 to 14.0 d.p.c.), cultured up to Passage 2 (P2), cryopreserved and thawed at each passage to be used as feeder cell layer for mESC and gESC cultures. In order to obtain the blastocyst sources for production of mESC and gESC lines, somatic cell nuclear transfer (in vitro) and in vivo flushing were carried out in this study. For isolation of the inner cell mass (ICM) from blastocyst, whole blastocyst culture, manual cut and laser dissection were compared among respective treatment groups to derive mESC and gESC lines. In murine, a total of 71 (ICR), 38 (CBA/ca), 22 (C57BL/6J) mESC lines were produced from 971, 758 and 709 murine blastocysts, respectively. Five blastocyst stages were cultured on the MEF with 3 ICM isolation techniques. ICM outgrowths were disaggregated by trypsin/EDTA (0.05%) and manual dissociation, cultured on new inactivated MEF in CO2 (5%) incubator at 37ºC. The attachment, primary ICM outgrowth and successful consecutive passages rates up to P3 were compared among the murine strains, blastocyst stages and iv ICM isolation techniques. There were significant differences (P<0.05) in successful passage rate at P3 between CBA/ca with ICR and C57BL/6J (19.81% vs. 9.00% and 8.50%), respectively, also mESC at Passage 1 (P1) for mid-, expanded- and hatching blastocyst stages versus early- and hatched blastocyst (45.35%, 52.79% and 43.01% vs. 27.88% and 24.53%), respectively. Manual cut ICM isolation technique consistently gave the highest attachment, primary ICM outgrowth and successful mESC P2 and P3 rates compared with whole blastocyst culture and laser dissection techniques (78.03% vs. 66.52% and 71.06%; 78.35% vs. 75.32% and 75.67%; 52.06% vs. 41.62% and 45.06%; 36.52% vs. 25.77% and 30.49%), respectively. In summary, the CBA/ca strain, expanded blastocyst stage and manual cut for ICM isolation techniques showed the optimal outcomes obtained in production of mESC lines. A total of 156 and 13 caprine blastocysts were obtained from in vitro- and in vivo-derived blastocyst, respectively. The in vivo-derived blastocsyts gave significant difference in production gESC lines at P3 compared with in vitro-derived blastocysts (91.67% vs. 20.83%). The caprine ICM outgrowths for gESC production were then disaggregated by trypsin/EDTA (0.05%) and manual dissociation and cultured on new inactivated MEF feeder cell layer in CO2 (5%) incubator at 37ºC. Manual cut for ICM isolation technique consistently gave the highest successful rates of gESC in P1 and P3 compared with whole blastocyst culture and laser dissection technique (71.28% vs. 39.58% and 43.89%; 35.04% vs. 12.50% and 23.33%), respectively. The mESC and gESC were stained to evaluate the expression of alkaline phosphates (AP) and positive results confirming the pluripotency of mESC and gESC were obtained. The ICM outgrowths for mESC were also characterised for Oct 4 and SSEA 1, whereas ICM outgrowths for gESC were characterised using Oct 4 and SSEA 3 and positive results were detected. It is concluded that ICM cells could be isolated from in vivo- and in vitro-derived murine and caprine blastocysts using whole blastocysts culture, manual cut and laser dissection v techniques and subsequently cultured to produce mESC and gESC lines as confirmed by positive expression of AP, Oct 4, SSEA 1 and SSEA 3. It is hoped that the findings obtained from this research will provide the fundamental information for future studies regarding establishment of ESC and MEF cell lines that can be potentially applied to overcome issues in livestock production, wildlife conservation and human regenerative medicine.